Conformation and activity of glucose oxidase on homogeneously coated and nanostructured surfaces - Seehuber, Andrea; Dahint, Reiner (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2013)
Protein unfolding and loss of protein function upon surface contact is a major problem in biotechnology and biomedicine. Using glucose oxidase (GOx) as a model protein, we investigated the impact of surface chemistry, topography, and confinement on enzyme activity, conformation, and affinity. A particular focus lay on the question whether the conformation of surface-bound proteins can be stabilized by embedding nanoscale adsorption sites, here in the form of monodisperse gold nanoparticles (AuNPs), into a protein-repelling matrix material. It was found that on homogeneous surfaces, GOx activity is generally lower than that in its native state and strongly affected by surface chemistry. Loss of activity is related to an increasing amount of β-sheets in the GOx secondary structure and a corresponding reduction of α-helical elements. In contrast, on AuNP surfaces, the effect of surface chemistry is negligible, and the amount of adsorbed protein only depends on particle size. The low activity of GOx on all nanostructures studied is again accompanied by an increase of β-sheet and a reduction of α-helical secondary structure. The major cause for protein unfolding on AuNPs thus seems to be the curvature of the surface. In addition, the data suggest that unfavorable orientation of the adsorbed enzyme also contributes to the loss of activity.
Gesehen am 12.08.2021